2002
DOI: 10.1177/106286060201700102
|View full text |Cite
|
Sign up to set email alerts
|

Academic Physicians and Complementary and Alternative Medicine: An Institutional Survey

Abstract: In order to assess attitudes, awareness, and behavior related to complementary and alternative medicine (CAM) among academic physicians, a questionnaire study was conducted with faculty in one of the largest teaching hospitals in the United States. The survey assessed attitudes toward and awareness of 11 CAM therapies in regard to patient usage and usefulness. The majority of respondents believed that only 20% or less of their patients used CAM. Respondents varied widely on level of knowledge/awareness of spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
2
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 8 publications
3
14
2
2
Order By: Relevance
“…In general, although their subjective levels of CAM knowledge were low, this study' s results show that in previous studies [12,20,21]. Taken together, these results emphasize the importance of CAM education in physicians'use of CAM in the future.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In general, although their subjective levels of CAM knowledge were low, this study' s results show that in previous studies [12,20,21]. Taken together, these results emphasize the importance of CAM education in physicians'use of CAM in the future.…”
Section: Discussionsupporting
confidence: 67%
“…However, considering that APs have a substantial impact on research, medical practice, and medical education related to CAM [20], it is reasonable to survey and compare APs and…”
Section: Discussionmentioning
confidence: 99%
“…(False=4) 26 These fi ndings are similar to those of other studies that assessed the self-reported knowledge levels of various CAM therapies among different health professionals. [6][7][8][9][10][11][12][13][14] The small proportion of participants who reported that they did not know the six basic CAM concept items indicates that most participating health educators were confi dent about their knowledge of those basic CAM concepts. The relatively small differences between mean scores and correct scores (i.e., knowledge gaps) for items assessing whether acupuncture is benefi cial in treating a variety of health conditions, the general defi nition of CAM, and whether there is suffi cient scientifi c evidence regarding CAM safety and effectiveness indicate that the participating health educators do possess an adequate level of knowledge regarding those basic CAM concepts.…”
Section: Discussionmentioning
confidence: 99%
“…For example, several studies asked participants to describe their level of knowledge of common CAM therapies on a Likert scale ranging from "no knowledge" to "a great amount of knowledge." [6][7][8][9] Other studies asked participants to state whether they had knowledge of a series of CAM therapies. [10][11][12][13][14] An extensive review of the extant literature identifi ed only one study that objectively measured the actual knowledge of several CAM therapies among health professionals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation